Pengaruh Penggunaan Media Cerita Bergambar Terhadap Keterampialan Membaca Nyaring Siswa Kelas IV SDN Watu Takula - Lende, Petrus; Malo, Efiana; Bili, Kristoforus Dowa (Lembaga Intelektual Muda (LIM) Maluku, 2025)
This study aims to determine the effect of using picture story media on the oral reading skills of fifth-grade students at SDN Watu Takula. This research is a quantitative study using an experimental method. The study uses a quasi-experiment in the form of a Nonequivalent Control Group Design. Data collection was carried out through observation and oral reading skill tests. Data analysis was conducted quantitatively using the t-test. Based on the results of the data analysis, it can be concluded that the average scores in the experimental class using picture story media are higher compared to the average scores of the control class taught without using picture story media. The average score of the experimental class is 79.37, while the control class is 48.44. The hypothesis test results indicate that there is an effect of using picture media on the learning outcomes of fourth-grade students at SDN Watu Takula, with the use of picture story media having a significant effect.